High-Performance Cathode/Electrolyte Interfaces for SOFC. (2nd June 2015) - Szász, Julian; Wankmüller, Florian; Wilde, Virginia; Störmer, Heike; Gerthsen, Dagmar; Menzler, Norbert H.; Ivers-Tiffée, Ellen
Abstract : High-performance oxygen electrodes for solid oxide fuel cells (SOFC) require a highly efficient material selection for the oxygen reduction reaction that takes places near the cathode/electrolyte interface. La1-x Srx Co1-y Fey O3-δ (LSCF) delivers fast oxygen-exchange kinetics and is therefore utilized as cathode material for high performing state-of-the-art anode-supported fuel cells. The main disadvantage of LSCF is its instability against Zr-based electrolytes. A diffusion barrier interlayer consisting of Gd doped cerium oxide (GDC) is therefore inserted to prevent the formation of an insulating SrZrO3 phase. This study presents new results on the importance of the GDC manufacturing conditions. A complex interaction of GDC with LSCF and YSZ during fabrication is found with a tremendous influence on the performance of the cathode/electrolyte interface of SOFCs.